ULYSSES observations of energetic particle acceleration and the superposed CME and CIR events of November 1992 - Lim,TL; Quenby,JJ; Reuss,MK; Keppler,E; Kunow,H; Heber,B; Forsyth,RJ (Annales Geophysicae, 1996)
Abstract. During November 1992, a series of forward and reverse shocks passed the ULYSSES spacecraft. Spectral and anisotropy measurements are reported for protons and alpha particles between 0.28 and 6 MeV observed by the Energetic Particle Composition Experiment, data recorded by the Magnetometer Experiment and the high-energy (2.7–300 MeV) proton data from the Kiel Electron Telescope. An analysis of energetic particle, plasma and magnetometer data from ULYSSES has allowed a unique study of the corresponding arrival of fare particles, particles within a corotating interaction region and particles transported with a coronal mass ejection. We present an analysis of these data in terms of possible diffusive shock acceleration but conclude that this is likely to be incompatible with the short transit time of the particles. Shock drift acceleration of particles with energies 0.3 MeV/nucleon or solar acceleration followed by particle trapping behind the shock front are alternative possibilities.